Control of three phase matrix frequency converters on base of first harmonics method in space with two time variables - Korotyeyev, I.Ye.; Klytta, M. (Технічна електродинаміка, 2012)
A procedure for the synthesis of control signals for three phase matrix frequency converters is presented. The procedure is based on extension of the space of one time variable to the space with two time variables. An expansion of control signals in Fourier series is use.